The Case of Herdade do Freixo do Meio in the Emergence of a Scientific Broadcasting Documentary Supported by Agricultural Reengineering - Lopes, Albino Anjos; Romana, Fernando Acabado; Sendim, Alfredo Cunhal (Archives of Business Research, 2024)
In the text, we identify what we call stages of a project that aims to be “innovative” of “scientific broadcasting documentary” organized in steps of a unique experience. The conditions of the case study are of a quasi-laboratory nature. The context is presented as that of an “agroforestry eco-archaeo-history” of the Mediterranean-peninsular settlement pattern. Instead of choosing a rationalist approach to reflect on the facts under discussion, we follow a Gabriel Garcia Marques approach to make common people experience the essence of what is at stake. But instead of a romance, we opt for choosing the strength of a space to explore, as can only be done on a tourist tour, placing the space (in the image of a character) at the centre of the narrative. The HFM space effectively tells a story that is radically different from the dominant narrative, and which makes sedentarization dependent on the so-called “cereal revolution”. In fact, this text seeks to describe a “conceptual journey”, in nine stages, deduced from our direct observation on the ground, complemented by several interviews with the actors mentioned in the text, covering around 6,000 years of settlement, in space of Herdade do Freixo do Meio (HFM), in Foros de Vale Figueira – municipality of Montemor o Novo, a property that allows to demonstrate the possibility of full sustainability (and viability) from all points of view, that is, from values based on the point of view of social, economic, demographic or ecological justice. The idealized tourist itinerary project (as a possible salable product) aims to amplify the remarkable work carried out at HFM, on the side of stimulating demand. This project aims to “help” publicize the collective action of actors in the agroforestry experience, and in this way, to consolidate itself, in turn, on the side of stimulating supply. Furthermore, in this consolidation of demand, a particular interest can be conceived from the study now proposed, as we think, analysing it from a third angle, that of its effectively “easy” repeatability across the interior territories of our country and not only.